Dysregulated Bile Transporters and Impaired Tight Junctions During Chronic Liver Injury in Mice - Pradhan-Sundd, Tirthadipa; Vats, Ravi; Russell, Jacquelyn O.; Singh, Sucha; Michael, Adeola Adebayo; Molina, Laura; Kakar, Shelly; Cornuet, Pamela; Poddar, Minakshi; Watkins, Simon C.; Nejak-Bowen, Kari N.; Monga, Satdarshan P.; et al. (Gastroenterology (New York, N.Y. 1943), 2018)
Liver fibrosis, hepatocellular necrosis, inflammation, and proliferation of liver progenitor cells are features of chronic liver injury. Mouse models have been used to study the end-stage pathophysiology of chronic liver injury. However, little is known about differences in the mechanisms of liver injury among different mouse models because of our inability to visualize the progression of liver injury in vivo in mice. We developed a method to visualize bile transport and blood-bile barrier (BBlB) integrity in live mice. C57BL/6 mice were fed a choline-deficient, ethionine-supplemented (CDE) diet or a diet containing 0.1% 3,5-diethoxycarbonyl-1, 4-dihydrocollidine (DDC) for up to 4 weeks to induce chronic liver injury. We used quantitative liver intravital microscopy (qLIM) for real-time assessment of bile transport and BBlB integrity in the intact livers of the live mice fed the CDE, DDC, or chow (control) diets. Liver tissues were collected from mice and analyzed by histology, immunohistochemistry, real-time polymerase chain reaction, and immunoblots. Mice with liver injury induced by a CDE or a DDC diet had breaches in the BBlB and impaired bile secretion, observed by qLIM compared with control mice. Impaired bile secretion was associated with reduced expression of several tight-junction proteins (claudins 3, 5, and 7) and bile transporters (NTCP, OATP1, BSEP, ABCG5, and ABCG8). A prolonged (2-week) CDE, but not DDC, diet led to re-expression of tight junction proteins and bile transporters, concomitant with the reestablishment of BBlB integrity and bile secretion. We used qLIM to study chronic liver injury, induced by a choline-deficient or DDC diet, in mice. Progression of chronic liver injury was accompanied by loss of bile transporters and tight junction proteins. [Display omitted]